Signatures of a Charge Density Wave Phase and the Chiral Anomaly in the Fermionic Material Cobalt Monosilicide CoSi - Schnatmann, Lauritz; Geishendorf, Kevin; Lammel, Michaela; Damm, Christine; Novikov, Sergey; Thomas, Andy; Burkov, Alexander; Reith, Heiko; Nielsch, Kornelius; Schierning, Gabi (Advanced Electronic Materials, 2020)
Materials with topological electronic states have emerged as one of the most exciting discoveries of condensed quantum matter, hosting quasiparticles with extremely low effective mass and high mobility. Weyl materials contain such topological states in the bulk and additionally have a non-trivial chiral charge. However, despite known quantum effects caused by these chiral states, the interplay between chiral states, and a charge density wave phase, an ordering of the electrons to a correlated phase is not experimentally explored. Indications for the formation of a charge density wave phase in the Weyl material cobalt monosilicide CoSi are observed. Furthermore, the typical signatures of the charge density wave phase together with typical signatures of Weyl fermions in magnetic field dependent electrical transport characterization are investigated. The charge density wave and the chiral contribution to the electrical magneto-transport are separated as well as a suppression of the charge density wave phase is observed in magnetic fields.
CRIS-Team Scopus Importer:2022-04-14
Keywords: charge density wave; chiral anomalies; cobalt silicide; quantum transport